PENINGKATAN MINAT BACA SISWA DI SMAN 4 MATARAM - Iskandar Iskandar; Halimatun Sa’adiah; Rizki Fauzi S. Beleng (UNIVERSITAS MUHAMMADIYAH MATARAM, 2022)
The development of information technology has an influence on students' reading interest. On the one hand IT provides access to abundant reading so that students can easily find information through the reading they need. On the other hand IT has an influence on students' lack of interest in reading because they are more interested in menus or features provided such as social media and games. Therefore, it is important for the library to increase reading interest, especially in the Library of SMA Negeri 4 Mataram. So it is necessary to carry out active participation in the field as a form of community service carried out in the school library. The purpose of this service is to provide an understanding of the importance of increasing students' interest in reading. The method used in this service is to design activity plans, socialize the importance of reading interest, socialize reading service programs in libraries, information retrieval training through OPAC, and conduct coaching or mentoring of students' reading interest. The results carried out in this service are First, the socialization of the importance of interest in reading and the reading service program in the library received a positive response as seen from the high enthusiasm of students. Second, training in searching for information or library materials through OPAC has an effect on student independence in obtaining the required reading material so that students can search for themselves in OPAC. Third, fostering or assisting students' reading interest through one hour of reading at school accompanied by lecturers, librarians and class teachers has a significant influence on students' reading interest at SMAN 4 Mataram. The assisted students are increasingly diligent in reading and are attracted to the library during free hours.